(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Socio-economic rights in the African Charter are ideal in transforming socio-economic conditions of Africa’s people and preserving their historical collective way of living. For these rights to achieve goals envisaged by the Charter, an innovative interpretation that engages relevant interpretative tools is required. This article argues that African philosophy is a potential interpretative tool that can contribute immensely to upholding the Charter’s object and purpose. Founded on the principles of collectiveness and togetherness of Africa’s people, African philosophy has the potential to enrich the meaning, scope and content of socio-economic rights and enable individuals to commune with others in all spheres of socio-economic activities. The article argues that engaging African philosophy in the interpretative process will guarantee individual and collective enjoyment of socio-economic rights to Africa’s people as understood in the African context. However, the supervisory organs of the African Charter have not effectively applied this significant interpretative tool in their socio-economic rights jurisprudence.